2015
DOI: 10.1515/agp-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Ordovician stratigraphy and fauna of the Anarak Region in Central Iran

Abstract: ABSTRACT:Popov, L.E., Hairapetian, V., Evans, D.H., Ghobadi Pour, M., Holmer, L.E. and Baars, C. 2015. Review of the Ordovician stratigraphy and fauna of the Anarak Region in Central Iran. Acta Geologica Polonica, 65 (4), 403-435. Warszawa.The Ordovician sedimentary succession of the Pol-e Khavand area, situated on the northern margin of the Yazd block, has important differences from those in other parts of Central Iran. It has been established that the presumably terminal Cambrian to Lower Ordovician volcano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“….32), Popov et al . () and Hairapetian et al . () mentioned, within the Chahgonbad Formation, a lower assemblage with brachiopods, cephalopods and ostracods (Schallreuter et al .…”
Section: Regional Faunas and Correlationmentioning
confidence: 91%
See 2 more Smart Citations
“….32), Popov et al . () and Hairapetian et al . () mentioned, within the Chahgonbad Formation, a lower assemblage with brachiopods, cephalopods and ostracods (Schallreuter et al .…”
Section: Regional Faunas and Correlationmentioning
confidence: 91%
“…In a different region of central Iran (Anarak; Fig. 6.32), Popov et al (2015) and Hairapetian et al (2015) mentioned, within the Chahgonbad Formation, a lower assemblage with brachiopods, cephalopods and ostracods (Schallreuter et al 2006) of Middle Ordovician age. In the upper third of the same formation, trilobites (Vietnamia cf.…”
Section: Iranmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies by Hairapetian et al (2015) and Popov et al (2015b) revealed that the lower Palaeozoic succession of the Anarak Region differs significantly from those in the other parts of Iran. In particular, it was confirmed that the presumably Furongian to Lower Ordovician Polekhavand Formation introduced in these papers has a sharp unconformable boundary with the underlying Doshakh metamorphic complex presumably of Cambrian age.…”
Section: Anarak Regionmentioning
confidence: 96%
“…The Middle to Upper Ordovician part of the succession has been assigned to the Chahgonbad Formation, which rests unconformably on the Polekhavand Formation and contains a bed of oolitic ironstones in its basal part. The Darriwilian to Katian age of the unit is based on brachiopod and trilobite faunas (Popov et al 2015b). Text- fig.…”
Section: Anarak Regionmentioning
confidence: 99%